El tema del tiempo en la "Expositio in physicam" de Walter Burley - Larre, Olga Lucía (Sapientia, 2009)
The purpose of this work is to reconstruct the itinerary of the immediate reaction of Walter Burley’s ultra realism in view of the criticism of Ockham’s nominalism, based on the physical theory and, in particular, on the topic of time. We believe that the comparative analysis of Ockham and Burley´s doctrines would shed some light on the history of the first and significant confrontations with the Ockham’s theory, seeking to shape a new intellection of the 14th century, where Burley would become an important figure by encouraging reflection on a figure such as Ockham. We focus our analysis on two topics: first, the one related to determining the concept of time and its distinction from movement; and second, the problem of the unity or plurality of times. The work tentatively proposes that both authors knew each other’s doctrines, that they reciprocally read and corrected them; and that the deep differences that appear in their systems must be found on a different gnoseo-ontological basis.